Multinational teams in the European Commission and the European Parliament - Neyer, Anne-Katrin (Forschungsergebnisse der Wirtschaftsuniversitaet Wien, 2018)
International public organizations, as the European Commission and the European Parliament, are under almost permanent political pressure to improve efficiency. While teamwork is considered to be a possible remedy, so far little research on effectiveness of multinational teams was undertaken in international public organizations. The purpose of this book is to identify the distinctive characteristics that influence multinational team performance in a public management context. Based on a qualitative research approach a complexity model of multinational team performance was developed. This model can be used as a checklist to identify possible problems in multinational teams. Additionally, managerial implications of how to deal with the inherent complexity of multinational teams are given.